Resting myocardial perfusion not coronary flow reserve predicts hibernating myocardium: implications for using resting myocardial contrast echocardiography versus dobutamine echocardiography for the detection of hibernating myocardium. (22nd September 2015) - Hickman, M; Burden, L; Senior, R
Abstract : Background: The relationship between resting myocardial perfusion, coronary flow reserve (CFR) and contractile reserve (CR) in hibernating myocardium (HM) remains unclear. This has not only pathophysiological implications but may impact on the optimum diagnostic technique for the identification of HM. Methods: Accordingly, 27 patients with severe symptomatic ischaemic cardiomyopathy (left ventricular ejection fraction 30 ± 10%) who were scheduled to undergo revascularisation underwent resting and vasodilator myocardial contrast echocardiography (MCE) and dobutamine echocardiography (DE). Resting myocardial perfusion parameters assessed were myocardial blood volume (A)(db), myocardial blood flow (β)(db/s), CFR (β stress/β rest) and CR (improvement in function during dobutamine). HM was defined as the improvement in resting function of a dysfunctional segment or the improvement of contractile function in a persistently dysfunctional segment during DE 3–6 months after revascularisation. Result: Of the 310 dysfunctional segments (17-segment left ventricular model) in 23 patients available for follow-up, 224 (74%) demonstrated HM. A and β were significantly reduced in HM (A 7.2 ± 2.3 and β 0.67 ± 0.56) compared with normal myocardium (A 8.1 ± 2.1 and β 0.85 ± 0.47, p<0.05, p<0.01, respectively) but was significantly higher compared with necrotic myocardium (A 4.4 ± 2.3 and β 0.43 ± 0.32, p<0.01, p<0.01, respectively). CFR, however, was similarly reduced (p = NS) in HM (1.3 ± 3.3) and necrotic myocardium (0.82 ± 3.2) compared with normal myocardium (1.68 ± 1.02, p<0.01). CR was directly related to CFR (p = 0.03) but not to resting myocardial perfusion. The sensitivity of MCE was 87% compared with 67% (p<0.001), with DE with similar specificity (67% vs 63%, respectively) for the detection of HM. Conclusion: Resting myocardial perfusion parameters but not CFR identifies HM. DE which assesses CR (which is influenced by CFR), thus underestimates HM compared with MCE.